1999
DOI: 10.1177/104063879901100205
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis Induced by Bovine Herpesvirus 5 and Protection by Prior Vaccination or Infection with Bovine Herpesvirus 1

Abstract: Abstract. Calves were intranasally challenged with bovine herpesvirus 5 (BHV5) and followed for the development of viral infection, clinical encephalitis, histologic lesions in the brain, and viral sequences in the trigeminal ganglia. Calves that were previously vaccinated with bovine herepesvirus 1 (BHV1, n ϭ 4) or previously infected with BHV1 (n ϭ 5) or that had not been exposed to either virus (n ϭ 4) were compared. No calf developed signs of encephalitis, although all calves developed an infection as indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
11

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 16 publications
4
51
1
11
Order By: Relevance
“…Mild or moderate nonsuppurative meningitis has been described in cases of BHV-5 infection in cattle (Lunardi et al 2009), restricted to the anterior and posterior cerebral cortex (Perez et al 2002). However, in previous cases of BHV-5 infection this lesion was not reported (Cascio et al 1999, Colodel et al 2002. Cases of BHV-5 infection with polymorphonuclear infiltration in the brain have been reported (Elias et al 2004, Rissi et al 2006, but this pathological finding was not observed in the present study.…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Acontrasting
confidence: 53%
“…Mild or moderate nonsuppurative meningitis has been described in cases of BHV-5 infection in cattle (Lunardi et al 2009), restricted to the anterior and posterior cerebral cortex (Perez et al 2002). However, in previous cases of BHV-5 infection this lesion was not reported (Cascio et al 1999, Colodel et al 2002. Cases of BHV-5 infection with polymorphonuclear infiltration in the brain have been reported (Elias et al 2004, Rissi et al 2006, but this pathological finding was not observed in the present study.…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Acontrasting
confidence: 53%
“…Indeed, a primary infection with BoHV-1 affords a cross-protection that protects cattle clinically against BoHV-5 superinfection [13,18]. This feature can explain the epidemiology of BoHV-5 infection in several continents.…”
Section: Preventionmentioning
confidence: 99%
“…O BHV-5, por sua vez, parece peculiar em sua distribuição; raras são as amostras de BHV-5 isoladas no hemisfério norte (D'Offay et al 1995, Cascio et al 1999 geográfica, talvez associada a particularidades não identificadas no manejo, tenha levado a que amostras daqueles estados apresentassem maior variabilidade antigênica do que as encontradas nos outros estados. Entretanto, a confirmação desta hipótese terá que aguardar a identificação de um maior número de isolamentos de vírus destas áreas específicas.…”
Section: Discus Discus Discus Discus Discussão São São São Sãounclassified
“…Até o presente, não é possível determinar a real prevalência de infecções por BHV-5, visto que testes sorológicos capazes de distinguir respostas frente a BHV-1 e BHV-5 ainda não se encontram disponí-veis. As infecções pelo BHV-5 são raras no hemisfério norte (D'Offay et al 1995, Cascio et al 1999, diferindo das observações na América do Sul. No Brasil, evidências acumuladas por grupos atuantes na área sugerem que uma significativa proporção de bovinos cujo diagnóstico sorológico havia sido estabelecido como BHV-1 eram provavelmente causadas por BHV-5 (Teixeira et al 1998, Heinlein et al 1993, Weiblen et al 1989.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified